Pipa and Gallienus - Estrada San Juan, Gabriel (Hyperboreus, 2023)
Princess Pipa of the Marcomanni, alleged wife or concubine of emperor Gallienus, is a character known to us through four references in three late sources. The information they provide is scarce and diﬃcult to interpret, despite the fact that she is an important part of the alliance formed between these Germanic people and the Empire. In this article, these passages are interpreted in detail, while trying to reconstruct the historiographical tradition and relating the contribution of modern scholars regarding the historical setting of the alliance and the possible bigamous marriage implied by one of the sources.